Pengaruh Penggunaan Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar IPS Di SD - Putri, Tiffa Ardiana; Zuardi, Zuardi; Amini, Risda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis resesrch purpose is to know the effect of using Problem Based Learning model toward study result of social sciences students in the fifth grade of Elementary school in 20 Lubuk Alung. The kind of this research wa quasi experiment type non equivalent control group desaign. To detemine the sample the research used purposive sampling. in this research there werw 40 students as the sample and 156 students as the populations. The result showed that tobtained > ttable (4,060 > 1,72) with α = 0,05 it can be cocluded that H0 was rejected and Ha was accepted, it means that there was signitificant effect of using PBL model  toward study result of social students in the fifth grade of elementary school in 20 Lubuk Alung. Key Words : PBL, Learning Outcomes, IPS